2010
DOI: 10.1638/2009-0143r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thiafentanil–Medetomidine for the Induction of Anesthesia in Emus (Dromaius novaehollandiae) Within a Wild Animal Park

Abstract: Fifteen adult emu (Dromaius novaehollandiae) anesthetic events were successfully undertaken with the use of thiafentanil oxalate (A3080) 0.175 mg/kg i.m. (SD 0.026) and medetomidine 0.092 mg/kg i.m. (SD 0.009) via remote injection. Following induction, the birds were transported to the clinic, where a venous blood gas sample was taken for analysis, which indicated a respiratory acidosis, with a mean arterial pCO2 of 54.46 mmHg (SD 9.31) and venous pH of 7.135 (SD 0.11), most likely due to moderate bradypnoea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The additional administration of diazepam caused both heart and respiration rates to decrease, which was expected because diazepam induces general depression of the central nervous system . The administration of medetomidine and isoflurane gas causes bradypnoea in ratites, resulting in respiratory acidaemia and low blood pH, which lead to further complications and require manual ventilation or supplementary oxygen . As veterinary support and supplies are often limited in the field, we argue that an anaesthetic that does not induce bradypnoea is preferable when anaesthetising large ratites not in captivity.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The additional administration of diazepam caused both heart and respiration rates to decrease, which was expected because diazepam induces general depression of the central nervous system . The administration of medetomidine and isoflurane gas causes bradypnoea in ratites, resulting in respiratory acidaemia and low blood pH, which lead to further complications and require manual ventilation or supplementary oxygen . As veterinary support and supplies are often limited in the field, we argue that an anaesthetic that does not induce bradypnoea is preferable when anaesthetising large ratites not in captivity.…”
Section: Discussionmentioning
confidence: 89%
“…Medetomidine has been shown to provide satisfactory sedation of captive southern cassowaries and emus ( Dromaius novaehollandiae ) and with the aid of the reversal agent, atipamezole, the birds recovered without the violent recovery and convulsions that accompanied other commonly used sedatives . Those findings surmise medetomidine to be the ideal drug for the chemical restraint of large ratites, but initial trials conducted by us showed that medetomidine was ineffective for wild southern cassowaries, because the long induction time (∼15 min) did not provide a suitable level of chemical immobilisation before the birds fled into the thick rainforest.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thiafentanil has been widely used for wildlife immobilisation on different species: nyala (Cooper et al, 2005), Lichtenstein's hartebeest (Citino et al, 2002), mule deer (Wolfe et al, 2004), emu (Cushing and McClean, 2010), Tibetan yak (Cushing et al, 2011), gaur (Napier et al, 2011), axis deer (Smith et al, 2006) and greater rhea (Ter Beest et al, 2012). The thiafentanil-azaperone combination for African buffalo (Syncerus caffer) immobilisation has been mentioned in books (Kreeger et al, 2002;West et al, 2008).…”
mentioning
confidence: 99%